PROPAGATION OF ARBUSCULAR MYCORRHIZAL FUNGI (AMF) SPORES FROM ARABICA COFFEE (Coffea arabica L.) PLANTATIONS IN BENER MERIAH REGENCY - Yusnizar, Yusnizar; Syafruddin, Syafruddin; Hifnalisa, Hifnalisa; Karim, Abubakar; Fikrinda, Fikrinda; Latifurrahmi, Latifurrahmi (Percetakan Umi Toaha Makassar, 2024)
Arbuscular Mycorrhizal Fungi (AMF) is a type of fungus that is capable of mutualistic symbiosis with plant roots. The presence of AMF can increase the availability of nutrients in the soil, especially the element P, expand the nutrient uptake area with the help of mycelium, plant resistance to disease and drought, and be able to produce growth hormones. These fungi can form a symbiotic relationship and increase the growth and productivity of coffee plants. This research aims to multiply AMF spores collected from the rhizosphere of Arabica coffee plants in Bener Meriah Regency using corn as a host plant. This research uses a descriptive method. Propagation of AMF spores collected from the rhizosphere of Arabica coffee plants using a single propagation method using zeolite media and corn host plants. Counting of AMF spores resulting from multiplication and observing AMF colonization on plant roots was carried out after the corn plants were stressed. Observation of the number of spores was carried out using the wet filtration isolation method and centrifugation technique (Brundrett et al., 1996). Observation of the percentage of AMF colonization on corn plant roots using the root staining method. Data analysis was carried out descriptively. The research results showed that from 44 AMF spores originating from the rhizosphere of Arabica coffee in Bener Meriah Regency, 111 AMF spores were obtained from propagation with a colonization percentage ranging from 0 – 81%. The largest number of spores were 11 spores resulting from multiplication originating from M44 spores, while the highest percentage of root colonization (81%) with very high criteria contained host roots colonized by M1 spores. A total of 12 AMF spores colonized the host roots with high to very high criteria. The research results showed that AMF spores from the rhizosphere of Arabica coffee in Bener Meriah Regency which were propagated by pot culture on zeolite media and corn as the host plant were relatively low with the percentage of root colonization varying from none to very high